Effect of Protected Kapok Seed Oil Supplementation on In Vitro Ruminal Lipid Status - Widiyastuti, Widiyanto; Soejono, M; Hartadi, H; Bachrudin, Z (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2009)
This investigation was conducted to study the influence of protected kapok seed oilÂ (KSO) supplementation on ruminal lipid status. Kapok seed oil (KSO), field grass (FG), Javanese Thin Tailed Sheep (JTTS) sheep rumen fluid, were used as experimental material. There were two treatment factors, namely : KSO supplementation as factor I, and KSO protection (throughout formation of Ca- salt after lipolysis by KOH) as factor II. Factor I consist of 4 supplementation levels, namely : 0% (S0); 5% (S1); 10% (S2), and 15% (S3), respectively, wheareas factor II consist of 5 protection levels, namely : 0% (P0); 25% (P1); 50% (P2); 75% (P3), and 100% (P4), repectivelly. Amount of 15 treatment combination were formed with control, namely without KSO supplementation and without protection (S0P0). The measured variables included : relative proportion of volatile fatty acids (VFAs), i.e. : acetic acid, propionic acid, and butyric acid. In addition, the iodine number (IN) and relative proportion of long chain fatty acid (LCFA), i.e. : stearic acid and linoleic acid )omega 6 polyunsaturated fatty acid) were also measured. Collected data were analyzed statistically by analysis of variance with factorial treatment pattern in completely randomized design. The result of this investigation showed that supplementation 10% or upper KSO without protection decreased asetis acid/propionic (A/P) ratio. Ratio of A/P tend increased again with protected KSO supplementation, but on 10 and 15% supplementation levels still lower than control (1.47â2.99 vs 3.36). Protected KSO supplementation increased the relative proportion of linoleic acid and unsaturation rate of ruminal fatty acid (P<0,05) with the higher iodine number, a long with enhancing of supplementation level. Relative proportion of linoleic acid and iodineÂ number (IN) in S1P0, S2P0, S2P3, S2P4 and S3P4 treatment groups were : 17,65 and 10,32; 33,07% and 18,67; 42,29% and 41,95; 45,01% and 47,40; 45,17and 50,99%, respectively. (Animal Production 11(2): 122-128 (2009)Â Key Words: supplementation, kapok seed oil, ruminal lipid status